1996
DOI: 10.1002/j.1556-6676.1996.tb01859.x
|View full text |Cite
|
Sign up to set email alerts
|

White Counselor Self‐Awareness: A Prerequisite for Developing Multicultural Competence

Abstract: This review of the literature examines White counselor self-awareness as an important variable in developing multicultural competence. The self-dimension discussed in this article includes worldview, cultural values, and racial identity. It is suggested that counselor self-awareness is a prerequisite to developing multicultural competence and that an in-depth understanding of these factors may improve the delivery of mental health services to culturally diverse client populations. he cultural value system inhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 28 publications
2
55
0
Order By: Relevance
“…Robinson and Howard-Hamilton also revealed that making assumptions based on a monocultural perspective, a view that diminishes an individual's personal and social reality, is potentially unethical practice and could cause psychological harm. Richardson and Molinaro (1996) reaffirmed what many prior writers have stated; namely, that becoming aware of one's own worldview and culture is a necessary precondition for escaping ethnocentrism. Overcoming one's own biases and prejudices recycles the old adage, "Counselor, know thyself."…”
Section: Multiple Identities and Culturesupporting
confidence: 84%
“…Robinson and Howard-Hamilton also revealed that making assumptions based on a monocultural perspective, a view that diminishes an individual's personal and social reality, is potentially unethical practice and could cause psychological harm. Richardson and Molinaro (1996) reaffirmed what many prior writers have stated; namely, that becoming aware of one's own worldview and culture is a necessary precondition for escaping ethnocentrism. Overcoming one's own biases and prejudices recycles the old adage, "Counselor, know thyself."…”
Section: Multiple Identities and Culturesupporting
confidence: 84%
“…Self-awareness requires a therapist's understanding of the interface between therapist and client worldviews; therapist self-examination of reactions to race, sexual orientation, and ageism along with issues of defensiveness, racial-identity attitudes, White privilege, and differential power status in therapy; and how these impact the client (Richardson & Molinaro, 1996;Roysircar, 2003). Self-assessment to identify attitudes and behaviors may include the use of self-report standardized measures, journaling, process notes, self-reflection skills, and critical incidents (Brislin, 1986;Carter, 2003;Pedersen, 1994;Roysircar et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…This is a particularly important exercise for White students, many of whom have never thought about their own race and its implications for relationships with others, especially people of color. The inclusion of theory and research related to White Racial Identity (Helms, 1995) or White Counselor Self-Awareness (Richardson & Molinaro, 1996) is critical in order for such an exercise to be effective with White students. Sue, h e n d o n d o , and McDavis (1992) wrote that ethical standards of multicultural competency for White students mean that they "understand how they may have directly or indirectly benefited from individual, institutional, and cultural racism (White identity development models)" (p. 482).…”
Section: Ct)mentioning
confidence: 98%